2012
DOI: 10.1155/2012/602401
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Repertoire of the Philippine Tarsier (Tarsius syrichta fraterculus) and Individual Variation of Long-Distance Calls

Abstract: We present the spectrographic description of the vocal repertoire of the Philippine tarsier (Tarsius syrichta fraterculus), a solitary living nocturnal primate for which a very limited information about acoustic communication exists to date. The majority of vocalizations were performed around sunset and, less frequently, at sunrise. We identified eight call types. Five calls recorded during communication between adults included three long-distance calls-loud call, smack-whistle, and whistle-then a soft locust-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Loud call, chirp, cheep (Řeháková-Petrů, Policht, et al, 2012) were recorded between 6 and 9 p.m. The next morning female was found high on a sleeping tree, the infant was not visible on the mother's body, in the afternoon it was found dead on the floor.…”
Section: Study Animals and Breedingmentioning
confidence: 99%
See 3 more Smart Citations
“…Loud call, chirp, cheep (Řeháková-Petrů, Policht, et al, 2012) were recorded between 6 and 9 p.m. The next morning female was found high on a sleeping tree, the infant was not visible on the mother's body, in the afternoon it was found dead on the floor.…”
Section: Study Animals and Breedingmentioning
confidence: 99%
“…However, most of them focus on tarsier species living on Sulawesi. To date only a few studies have investigated the biology, ecology, and behavior of the Philippine tarsier (Dagosto & Gebo, ; Dagosto, Gebo, & Dolino, ; Jachowski & Pizzaras, ; Lovegrove et al, ; Neri‐Arboleda, Stott, & Arboleda, ; Řeháková, ; Řeháková‐Petrů, Peške, & Daněk, ; Řeháková‐Petrů, Policht, & Peške, ) and the Philippine tarsier remains one of the least known primates. Tarsiers are nocturnal primates, active from dusk to dawn.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Robinson (1979) found that in Callicebus cupreus duets are achieved by females and males alternating the different parts (Robinson 1979), but also that females exhibit lower-pitched bellows than males. Tarsiers also show sexually dimorphic calls, further characterized by individual variation (Řeháková-Petrů et al 2012).…”
Section: Introductionmentioning
confidence: 99%